Perilaku Bully Siswa Menurut Pandangan MUI Kabupaten Langkat (Studi Kasus di MIN 5 Langkat) - Afifuddin Al Ishlah; Sudianto; Suaib Lubis (Journal Smart Law, 2024)
One negative form of social interaction between students is bullying. Bullying is considered inappropriate or deviant behavior because it has serious consequences. The purpose of this research is to explore bullying behavior among students, its psychological effects on the victims, the psychological effects on the perpetrators, and the perspective of the MUI (Indonesian Ulema Council) Langkat on bullying behavior at MIN 5 Langkat. This study uses a qualitative research method, which is descriptive and analytical, with data in the form of words, sentences, diagrams, or images rather than statistical numbers. The data collection techniques used are observation, interviews, and documentation. The data analysis technique involves analyzing the data simultaneously during the data collection process. The research results show that: first, the most common forms of bullying at MIN 5 Langkat are verbal and physical bullying. Second, the psychological effects on victims of bullying include disruptions in learning, social interactions, and personal development. Victims of bullying become fearful, withdrawn, lack enthusiasm for school, suffer from low self-confidence, have difficulty concentrating, and experience a decline in academic performance. Third, the psychological effects on perpetrators of bullying at MIN 5 Langkat impact their academic performance and social relationships. Fourth, MUI Langkat's view of bullying behavior at MIN 5 Langkat, namely that bullying behavior at MIN 5 Langkat is still in the mild category, but in Islam it does not allow and does not tolerate bullying behavior, therefore MUI Langkat hopes that the madrasah will take several actions to reduce bullying behavior. even to the point where it no longer exists at MIN 5 Langkat.